Forest fires, woodland caribou and land use policies in northwestern Ontario (Rangifer tarandus) - Kutas, Brian Frederick (Scholars Commons @ Laurier, 2004)
Woodland caribou (Rangifer tarandus caribou) are a threatened species in Ontario's boreal forest. Caribou require habitat that supports appropriate forage, including large areas of lichen rich forests. This research examines two dynamics that influence woodland caribou habitat in northwestern Ontario. These dynamics are forest fires and land use policies. The effects of forest fires are assessed quantitatively at both the ecosite and landscape scales within Woodland Caribou Provincial Park. Land use policy and management activities are evaluated using a case study and a policy analysis of protected area and forest management approaches to woodland caribou conservation in this region. Forest fires in Woodland Caribou Provincial Park exert tremendous influence on woodland caribou habitat. However, they vary significantly in their ecological effects and return intervals. Fire severity plays an important role in determining both structure and composition of forest communities, shaping forest openings, duff characteristics, and how terrestrial lichen (an important food source for woodland caribou) recolonize an area after a burn. Results show that the amount of terrestrial lichen able to regenerate varies depending upon canopy openness and duff accumulation on V30 sites within Woodland Caribou Provincial Park. The amount of area burned within the park (measured by decade) in the 20th century varied dramatically from 319 ha in the 1950’s to over 106,000 ha in the 1980’s. These variations in site characteristics and stands of suitable ages have important implications for management and policy development. Forests suitable for woodland caribou habitat in this portion of Ontario are not in equilibrium. Land use policies intended to conserve caribou in this region must incorporate concepts of non-equilibrium forest dynamics. Management and policy development related to the conservation of woodland caribou is largely absent in Ontario Parks, due to a lack of information and limited strategic vision. The Forest Division of ...